Implementasi Manajemen Perpustakaan Dalam Meningkatkan Minat Literasi Siswa Di SMK Islam Nurul Hikmah Sangatta - Mukrima; Ningsih, Rina Novita (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research aims to analyze and evaluate the library management at SMK Islam Nurul Hikmah Sangatta with the objective of providing improvement recommendations. The research approach employed is qualitative with a case study method. Informants in this study include library staff, teachers, and students. The data collection techniques utilized are interviews and direct observation of library facilities and services. The collected data were analyzed qualitatively using thematic analysis techniques. The research findings indicate that library management at the mentioned vocational school faces challenges primarily in terms of resource availability, infrastructure, collection management, and library services. Improvement recommendations include adequate budget allocation, staff training, active involvement of all school members, implementation of information technology, and periodic evaluation. The implications of this research are expected to enhance the quality of library services and student reading interest, thereby positively contributing to academic achievement at SMK Islam Nurul Hikmah Sangatta.